2008
DOI: 10.1111/j.1468-1331.2008.02304.x
|View full text |Cite
|
Sign up to set email alerts
|

Mastery, functional disability and perceived health status in patients with multiple sclerosis

Abstract: Mastery, functional disability and perceived health status in patients with multiple sclerosis Krokavcova, M.; Nagyova, I.; van Dijk, J. P.; Rosenberger, J.; Gavelova, M.; Middel, B.; Gdovinova, Z.; Groothoff, J. W.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
5
24
0
Order By: Relevance
“…Compared with these previous studies, which reported the number of years since MS diagnosis ranging from 8 to 19 years,39 40 our participants have been diagnosed with MS for 24.8 (±10) years. Our respondents’ level of education aligns with most other studies of people with MS 39–41 43. The group is fairly well educated which is not surprising considering characteristics of people who respond to surveys in general 45.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Compared with these previous studies, which reported the number of years since MS diagnosis ranging from 8 to 19 years,39 40 our participants have been diagnosed with MS for 24.8 (±10) years. Our respondents’ level of education aligns with most other studies of people with MS 39–41 43. The group is fairly well educated which is not surprising considering characteristics of people who respond to surveys in general 45.…”
Section: Discussionsupporting
confidence: 80%
“…When compared with the Canadian population,33 fewer of our respondents had advanced education including postsecondary degrees and postgraduate degrees. Furthermore, only about 10% of our sample was employed in any capacity which is substantially lower than other studies of older people with MS 38 40 43. Since maintaining employment is associated with better quality of life, at least in younger people with MS,43 factors associated with employment and retirement as one ages with MS will be an important area of future study.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, Pearlin, Nguyen, Schieman, and Milkie (2007) noticed that extended education would indirectly influence the lifecourse mastery of older people 'through the greater occupational and financial opportunities' provided by education after high school (p. 173). Other authors indicated that although mastery is responsive to circumstances, it can also operate as a capacity (Skaff et al, 1996): it might buffer the impact of decrease in physical health on older people's well-being (Jonker, Comijs, Knipscheer, & Deeg, 2009), and it could buffer against the anxiety related to disability problems (Krokavcova et al, 2008). Furthermore, it was frequently reported that higher mastery levels are positively associated to physical and mental health outcomes, for example to lower risks of decline in functional ability (Kempen, Ranchor, Van Sonderen, Van Jaarsveld, & Sanderman, 2006), or to less depression (Krokavcova et al, 2008).…”
Section: Literature Overviewmentioning
confidence: 99%
“…Other authors indicated that although mastery is responsive to circumstances, it can also operate as a capacity (Skaff et al, 1996): it might buffer the impact of decrease in physical health on older people's well-being (Jonker, Comijs, Knipscheer, & Deeg, 2009), and it could buffer against the anxiety related to disability problems (Krokavcova et al, 2008). Furthermore, it was frequently reported that higher mastery levels are positively associated to physical and mental health outcomes, for example to lower risks of decline in functional ability (Kempen, Ranchor, Van Sonderen, Van Jaarsveld, & Sanderman, 2006), or to less depression (Krokavcova et al, 2008). Other researchers explained that a given level of control could be retained despite health decline; mainly through processes of selection, optimisation, and compensation (Baltes & Baltes, 1990) or through accommodative coping (Brandtstädter & Rothermund, 1994).…”
Section: Literature Overviewmentioning
confidence: 99%
“…The study sample consisted of two age subgroups of people with MS: a younger group aged 18-44 years (< 45 years) and an older group aged 45-61 years (Z 45 years). The age cut-off point of 45 years in this sample was based on previous studies in people with MS in age cohorts 18-45 and 45-90 years (Garcia and Finlayson, 2005;Krokavcova et al, 2008), and on the study mode (range 18-61 years).…”
Section: Sociodemographic Datamentioning
confidence: 99%